Improved Perturb and Observation Maximum Power Point Tracking Technique for Solar Photovoltaic Power Generation Systems - Manoharan P.; Subramaniam U.; Babu T.S.; Padmanaban S.; Holm-Nielsen J.B.; Mitolo M.; Ravichandran S. (Institute of Electrical and Electronics Engineers Inc., 2023)
DC-DC converters; Maximum power point trackers; Photovoltaic cells; Solar power plants; Tracking (position); Computational burden; Mathematical expressions; Maximum power point; Maximum Power Point Tracking; Maximum power point tracking techniques; Photovoltaic systems; Solar photovoltaic power generations; Variable step size methods; Solar power generation